Life writing: Straddling fact and fiction - Zaman, Tabassum (BRAC University, 2010)
Traditionally any autobiographic writing is expected to document past in retrospect just like history. But memoirs like Michael Ondaatje’s Running in the Family and Sheila Ortiz Taylor and Sandra Ortiz Taylor’s Imaginary Parents go against this traditional expectation both in form and content and while doing so they question the traditional idea of autobiographic writing as well as history. Through the atypical way they search for truth these memoirs have made us re consider the traditional expectation from this genre. While reconstructing the respective family history these two books deconstruct the general understanding of documented history as a centripetal, teleological narrative, something that projects absolute, objective reality.